Bentuk Tuturan Persuasif dalam Pidato Sandiaga Uno - Amelia Witra (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study discusses the use of persuasive speech forms in Sandiaga Uno's speech at a public lecture at the Islamic University of Riau. The purpose of this study is to reveal the use of persuasive speech forms in Sandiaga Uno's speech at a public lecture at the Islamic University of Riau. This type of research is a qualitative research with descriptive method. Descriptive means research that is carried out solely based on existing facts or phenomena that are empirically alive in the speaker. This qualitative research aims to produce descriptive data in the form of persuasive speech in Sandiaga Uno's speech at the Islamic University of Riau. The data analysis technique of this research is based on the interactive technique of Miles and Huberman. Through this model, analysis activities are carried out through four stages of activities, namely (a) data collection, (b) data reduction, (c) data presentation, and (d) drawing conclusions and final results. Based on the results and discussion, it can be concluded that the form persuasive speeches in Sandiaga Uno's speech at the Islamic University of Riau found twenty-five persuasive utterances in the form of assertive, seventeen directive utterances, ten expressive utterances, seven commissive utterances and two declarative utterances. Keywords: Form, persuasive speech, speech.